2015
DOI: 10.1007/s00198-015-3388-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms and association with medication use patterns, adherence, treatment satisfaction, quality of life, and resource use in osteoporosis: baseline results of the MUSIC-OS study

Abstract: SummaryThe Medication Use Patterns, Treatment Satisfaction, and Inadequate Control of Osteoporosis Study (MUSIC-OS) is a prospective, observational study of women with osteoporosis in Europe and Canada. At baseline, patients with gastrointestinal symptoms reported lower adherence to osteoporosis treatment, treatment satisfaction, and health-related quality of life, than those without gastrointestinal symptoms.IntroductionThe aim of the study was to examine gastrointestinal (GI) symptoms and the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
(41 reference statements)
2
12
0
4
Order By: Relevance
“…However, discontinuation is not directly comparable to the medication-taking behaviors assessed by the ADEOS questionnaire. Such behaviors were assessed using ADEOS by the MUSIC OS study in Europe and Canada (MUSIC OS-EU), which found that treated osteoporosis patients with GI events had lower ADEOS scores than those without GI events (adjusted least squares mean difference −0.43; P  < 0.001) [27]. This result is consistent with the findings of the MUSIC OS-AP study (adjusted least squares mean difference −0.348).…”
Section: Discussionsupporting
confidence: 66%
“…However, discontinuation is not directly comparable to the medication-taking behaviors assessed by the ADEOS questionnaire. Such behaviors were assessed using ADEOS by the MUSIC OS study in Europe and Canada (MUSIC OS-EU), which found that treated osteoporosis patients with GI events had lower ADEOS scores than those without GI events (adjusted least squares mean difference −0.43; P  < 0.001) [27]. This result is consistent with the findings of the MUSIC OS-AP study (adjusted least squares mean difference −0.348).…”
Section: Discussionsupporting
confidence: 66%
“…Our initial cohort of 24,571 patients (20,956 women [85.3%] and 3614 men [14.7%]; mean [SD] age = 84 [ years; 51% with moderate‐to‐severe cognitive impairment) included 18,869 bisphosphonate users and 5702 calcitonin users (Supplementary Figure S1). Before matching, bisphosphonate users were more likely to be younger, female, and nonwhite, and have received a dual‐energy X‐ray absorptiometry scan (Table ; Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 88%
“…Of these, 2545 patients remained eligible for analysis at month 12 of whom 535 were new users and 2010 were experienced users. The baseline demographic and clinical characteristics of the study sample have been reported elsewhere [ 32 ]. Briefly, the mean age of the study population was 69.4 years, and about half the patients (49.4%) had a history of osteoporotic fracture.…”
Section: Resultsmentioning
confidence: 99%